APLIKASI SISTEM INFORMASI GEOGRAFIS UNTUK PENGEMBANGAN KAWASAN STRATEGIS PARIWISATA PANTAI BILATO DI KABUPATEN GORONTALO (Geographic Information System Application for Strategic Tourism Development Areas of Bilato Beach in Gorontalo District) - Elpin Ibrahim; Ivan Taslim; Ahmad Syamsu Rijal (Jurnal Sains Informasi Geografi, 2018)
Abstract - This study aims to create a concept or strategy for the development of Strategic Tourism Area of Bilato Beach located in Gorontalo Regency Gorontalo Province. The planning strategy for the development of Bilato Beach Strategic Area in this research is based on the questionnaire and interview method with the field survey. The results of the interview will be processed using SWOT analysis which further utilizes Geographic Information System (GIS) application with ArcGIS 10.1 device for mapping of tourism development of Bilato Beach. In the result of observation at research location and interview (questionnaire) processed with SWOT approach obtained information about research location, such as white sand along the coastal landscape with the calm sea (Strengths). It's just that as a tourist attraction Bilato Beach has lack of adequate facilities, lack of government attention to the manager both in terms of financial aid and tourism publication (Weaknesses). In terms of Opportunities, Bilato Beach can be a source of income and business community, it is also supported by the terms of affordability/accessibility is quite easy. However, Bilato Beach as a tourist spot also has threats such as community activities and visitors that can be damage the natural habitat at the research location and also the many tourist attractions that make the competition in attracting the tourists. The conclusion of this SWOT analysis result is that Bilato Beach which has been designated as Tourism Strategic Area in Gorontalo Regency according to Province Regulation of Gorontalo Regency No. 4, 2011 still has many shortcomings in terms of tourism facilities and government attention in terms of publication. Keywords: tourism, strategic development, gis, swot analysis, bilato beach, gorontalo Abstrak – Penelitian ini bertujuan untuk membuat konsep atau strategi pengembangan Kawasan Strategis Pariwisata Pantai Bilato yang berada di Kabupaten Gorontalo. Strategi yang digunakan pada penelitian ini berdasarkan metode wawancara dan survai lapangan. Hasil dari wawancara akan diolah menggunakan analisis SWOT yang selanjutnya memanfaatkan aplikasi Sistem Informasi Geografis (SIG) dengan perangkat ArcGIS 10.1 untuk pemetaan pengembangan wisata Pantai Bilato. Pada hasil observasi di lokasi penelitian dan wawancara (kuisioner) yang diolah dengan pendekatan SWOT diperoleh informasi tentang lokasi penelitian, diantaranya adalah pasir putih sepanjang bentang alam pantai dengan laut yang tenang (Kekuatan). Hanya saja sebagai tempat wisata Pantai Bilato memiliki kekurangan dari segi fasilitas yang memadai, tidak adanya perhatian pemerintah terhadap pengelola baik dari segi bantuan dana maupun publikasi wisata (Kelemahan). Dari segi Peluang, Pantai Bilato bisa menjadi sumber pendapatan dan usaha masyarakat, hal ini juga didukung oleh segi keterjangkauan yang cukup mudah. Meski demikian Pantai Bilato sebagai tempat wisata juga mempunyai Ancaman seperti aktifitas masyarakat dan pengunjung yang dapat merusak habitat alami di lokasi penelitian dan juga banyaknya tempat wisata yang menjadikan persaingan dalam menarik minat para wisatawan. Kesimpulan dari hasil analisis SWOT ini adalah bahwa Pantai Bilato yang sudah ditetapkan sebagai Kawasan Strategis Pariwisata di Kabupaten Gorontalo menurut PERDA Provinsi Gorontalo No. 4 Tahun 2011 masih memiliki banyak kekurangan dari segi fasilitas wisata dan perhatian pemerintah dalam hal publikasi. Kata kunci: pariwisata, strategi pengembangan, sig, analisis swot, pantai bilato, gorontalo